2021
DOI: 10.1371/journal.pone.0240874
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analyses of Artemisia extracts on Plasmodium falciparum suggest a complex antimalarial effect

Abstract: Dried-leaf Artemisia annua L. (DLA) antimalarial therapy was shown effective in prior animal and human studies, but little is known about its mechanism of action. Here IC50s and ring-stage assays (RSAs) were used to compare extracts of A. annua (DLAe) to artemisinin (ART) and its derivatives in their ability to inhibit and kill Plasmodium falciparum strains 3D7, MRA1252, MRA1240, Cam3.11 and Cam3.11rev in vitro. Strains were sorbitol and Percoll synchronized to enrich for ring-stage parasites that were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…The sexual stage includes male and female gametocytes that can reside in the blood for some time acting as a parasite reservoir and are responsible for asymptomatic malaria. A. annua and A. afra tea infusions kill both blood asexual 5,6,84 and gametocyte stages 5,6 in vitro , results that corroborate clinical observations. 65,85,86 Recently, Ashraf et al 5 showed that tea infusions of the artemisinin-deficient species, A. afra , were more effective than artemisinin-containing A. annua against both rings and schizonts, and even more effective than dihydroartemisinin (DHA).…”
Section: Therapeutic Examplessupporting
confidence: 79%
See 2 more Smart Citations
“…The sexual stage includes male and female gametocytes that can reside in the blood for some time acting as a parasite reservoir and are responsible for asymptomatic malaria. A. annua and A. afra tea infusions kill both blood asexual 5,6,84 and gametocyte stages 5,6 in vitro , results that corroborate clinical observations. 65,85,86 Recently, Ashraf et al 5 showed that tea infusions of the artemisinin-deficient species, A. afra , were more effective than artemisinin-containing A. annua against both rings and schizonts, and even more effective than dihydroartemisinin (DHA).…”
Section: Therapeutic Examplessupporting
confidence: 79%
“…While artemisinin is well-established as a potent bioactive molecule with significant antimalarial activity, a growing number of studies have shown that there is considerable antimalarial activity from the plant that extends beyond artemisinin. For example, the studies already described in Section 4.1 on malaria 5,6,65,84–86 clearly demonstrate that artemisinin is not the sole antimalarial molecule in A. annua . In fact, Ashraf et al , 2022 showed that artemisinin-free A. afra has potent antimalarial activity.…”
Section: Is Artemisinin the Sole Artemisia Therapeuticmentioning
confidence: 95%
See 1 more Smart Citation
“…This kit, based on AuNPs, indicates the presence of the protein by the formation of a ring that can be analyzed visually. Hence, this kit can be used to detect malarial parasites [ 58 ].…”
Section: Metal-based Nanoparticles and Their Antiparasitic Significancementioning
confidence: 99%
“…The present study concerns ZnONPs biosynthesized from plant extracts (Artemisia annua L.) used as a bio-reducer. Artemisia annua L. is known for its medical value and the extracts from its leaves are believed to have organic molecules that have antioxidant activities to help reducing zinc to nanoparticles [31,32].…”
Section: Introductionmentioning
confidence: 99%